Techno-Economic Analysis of the Production of Magnesium Oxide Nanoparticles Using Sol-Gel Method - Anisa Noorlela; Asep Bayu Dani Nandiyanto; Risti Ragadhita; Meli Fiandini; Tedi Kurniawan (Journal of Mechanical Engineering, Science, and Innovation, 2023)
The purpose of this research is to determine the feasibility of a project in producing magnesium oxide (MgO) nanoparticles using the sol-gel method and to evaluate it from a technical and economic point of view. The sol-gel method is a method that is often used by industry because the process is simpler. Assessment from a specialized point of see is done by calculating the stoichiometry, whereas assessment from a financial viewpoint is decided by a few parameters, such as deciding Gross Profit Margin (GPM), predicting Payback Period (PBP), predicting Cumulative Net Present Value (CNPV), etc. The results of the technical analysis appear that the overall fetched of the gear to create 1,875 kg of MgO nanoparticles per day is 45,373 USD. Payback Period analysis appears that the venture pays off after more than three a long time. This venture is able to compete with PBP capital advertise measures since the venture will return in a brief time. Based on the economic evaluation, it can be concluded that this project is very promising if it is anticipated that losses will occur due to changes in several ideal conditions. The result of this study about are anticipated to be a reference for building more economical, efficient and high-demand MgO nanoparticle production projects.